Environmental degradation and municipal solid waste management in Eket- Nigeria (2012)
Environmental degradation is the deterioration of the environment through the depletion of resources such as air, water, soil and the destruction of ecosystems. Waste management involves collection, transport, processing, recycling or disposal, and monitoring of waste materials. These methods include; Source reduction, recycling, incineration, composting, landfilling, anaerobic digestion. Four major markets were selected in Eket to ascertain the quantity and type of waste generated to proposed the method of waste management. Of the total waste generated, 82% of the solid waste originate from markets and households while about 18% are from commercial and institutional or industrial premises. Of the waste from markets and households, a substantial proportion consist of various putrescible materials, paper, metal, glass, textiles, rubber, leather, wood, vegetable, dust and sand. Anaerobic digester was designed to help in this scenario. Some equations were generated for the design. Some constraints in the management of waste in Eket and potential health hazard were critically analysed. Recommendations were made for the construction of the biogas plant.